Temporal dynamics of Apis mellifera (Hymenoptera: Apidae) during flowering in indeterminate soybean (Glycine max) - de Souza, Ellen Patrícia; Degrande, Paulo E.; Barbosa, Vinicius O.; Alves Junior, Valter V.; Malaquias, Jose B. [UNESP] (FapUNIFESP (SciELO), 2023)
Soybean varieties with indeterminate growth habit are widely used in the state of Mato Grosso do Sul and are characterized by not having well-defined phenological stages. Due to the importance of bee conservation, studies on the frequency and time of visitation in indeterminate soybean are needed. Samples were collected in a 4-ha plot of soybeans not treated with insecticides. Sampling was carried out at random spots, throughout the flowering period, starting at 08h:00min, during 15 min/hour, successively until 16h:00min. Generalized Linear Models were generated and the Poisson regression model provided the best fit, reflecting the significant differences revealed by the deviance analysis. The association between bees and climatic variables was tested with the Spearman’s correlation. The temporal pattern of bee visitation was independently influenced by flowering period and time of day. However climatic variables did not influence significantly bee visitation rate. In the first days of flowering, bees were more abundant, especially between 10h and 15h. These results have practical implications in the maintenance of this species during soybean management practices, contributing to a balanced coexistence between beekeepers and soybean growers, by avoiding applications of phytosanitary products during the periods of high bee visitation.
Keywords: bee; behavior; foraging; visiting time